STRATEGI PENATALAKSANAAN TENAGA PERAWAT UNTUK PENANGGULANGAN PEMASUNGAN DI DINAS KESEHATAN KOTA PALEMBANG - Siahaan, Basa Tiur Mida (Direktorat Riset dan Pengabdian Kepada Masyarakat Universitas Bina Darma, 2018)
This study aims to determine and analyze internal factors and factors external management of nurses in overcoming the management and recommending the management strategies that need to be implemented to complete the treatment. Nurse management factors that occur, internally include not setting the standard of mental nursing care, nursing staff education is not in accordance with applicable regulations, double duty burden given by the leader and the absence of a safeguard management guide that will be used as an implementation guide, while external factors include the number of people with mental disorders will increase community stigma against mental disorders, families who cover themselves in dealing with the problem of mental disorders, the choice of practice to cope with mental disorders. influential in overcoming storage. The analysis technique used in analyzing the influential factors in this study is the SWOT analysis approach